Temperature dependence of polymer melt viscosity obtained based on DSC data and the consistency between thermodynamic and kinetic fragility - Fang, Chenghui; Chen, Huanhuan; Zhou, Juan; Chen, Liping; Guo, Zichao; Chen, Wanghua (Journal of applied polymer science, 2024)
The viscosity of the polymer melt has an impact on both the processing and properties of the product. However, conventional viscosity measurement methods have limitations such as strict testing conditions, large sample sizes, and long response times. This paper proposes a simplified method that utilizes differential scanning calorimetry to determine the viscosity–temperature relationship of the polymer melt. The research subjects consist of four noncrystalline polymers and five crystalline polymers. A new thermodynamic fragility formula of crystalline polymer is obtained. Additionally, high‐temperature limiting viscosity shows a good linear relationship with fragility. Compared with the traditional viscosity measurement, this method is a simpler and more effective way to model the viscosity of polymer melt and has broad prospects in application. Temperature dependence of polymer melt viscosity obtained by DSC.